Emodin ameliorates rheumatoid arthritis by promoting neutrophil apoptosis and inhibiting neutrophil extracellular trap formation. (August 2019) - Zhu, Mengmeng; Yuan, Kai; Lu, Qingyi; Zhu, Qingqing; Zhang, Shan; Li, Xiaohong; Zhao, Lu; Wang, Hesong; Luo, Guangbin; Wang, Ting; Huang, Guangrui; Xu, Anlong
Highlights: Emodin alleviated AA by reducing neutrophil infiltration and proinflammatory cytokine expression. Emodin promoted neutrophil apoptosis. Emodin inhibited neutrophils autophagy and NETosis. Abstract: Rheumatoid arthritis (RA) is a chronic, systemic, synovitis-based inflammatory disease with unknown etiology. Neutrophils play important roles in the pathogenesis of RA. Apoptosis and NETosis of neutrophils are two major mechanisms of programmed cell death that differ in their morphological characteristics and effects on the immune system. In rheumatoid arthritis, delayed neutrophil apoptosis amplifies the inflammatory response; and massive release of NETs and their components may cause tissue damage and provide self-antigens. Emodin is a natural anthraquinone derivative that occurs in many widely used Chinese medicinal herbs. In this study, we evaluated the effect of emodin on a murine adjuvant-induced arthritis (AA) model of RA in vivo and on neutrophil apoptosis and NETosis in vitro . Our results show that emodin alleviated AA by reducing neutrophil infiltration and proinflammatory cytokine (interleukin-6, interferon-gamma and tumor necrosis factor-α) release. Emodin promoted apoptosis and inhibited autophagy and NETosis in neutrophils. These findings indicate that emodin represents a potential therapeutic agent for RA.